A new endemic scorpion species from the Somuncura Plateau, in northern Patagonia (Scorpiones, Bothriuridae) - Ojanguren-Affilastro, Andrés Alejandro (Zootaxa, 2007)
A new scorpion species from Argentina, Bothriurus ceii n. sp., is described. This species belongs to the patagonicus group, which includes Bothriurus patagonicus Maury 1969 and several undescribed species from Patagonia. Bothriurus ceii n. sp. is endemic to the upper level of the Somuncura plateau, which shows characteristics of the Patagonic phytogeographyc province, whereas the surrounding area belongs to the Monte phytogeographyc province. Bothriurus ceii n. sp. can be distinguished from the rest of the species of the patagonicus group because it lacks the VSM and VL carinae of sternite V and metasomal segment I, which are present in the rest of the species of the group.